2014
DOI: 10.1021/jm500026w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Nonbasic Melanin Hormone Receptor 1 Antagonist as an Antiobesity Clinical Candidate

Abstract: Identification of MCHR1 antagonists with a preclinical safety profile to support clinical evaluation as antiobesity agents has been a challenge. Our finding that a basic moiety is not required for MCHR1 antagonists to achieve high affinity allowed us to explore structures less prone to off-target activities such as hERG inhibition. We report the SAR evolution of hydroxylated thienopyrimidinone ethers culminating in the identification of 27 (BMS-819881), which entered obesity clinical trials as the phosphate es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…The results indicate that MCH 1 receptor antagonism could influence appetite in humans, but the therapeutic potential of MCH 1 receptor as a target could not be evaluated because of limited CNS exposure. Only scarce information is available in the public domain from a 28 day phase I wt loss study with BMS‐830216 (a prodrug of BMS‐819881) (Washburn et al , ) (an overview of the observed findings is available at http://www.ncats.nih.gov/files/BMS-830216.pdf). No decrease in body wt or food intake could be observed in the study, but no data on the CNS behaviour of BMS‐830216/BMS‐819881 in man have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that MCH 1 receptor antagonism could influence appetite in humans, but the therapeutic potential of MCH 1 receptor as a target could not be evaluated because of limited CNS exposure. Only scarce information is available in the public domain from a 28 day phase I wt loss study with BMS‐830216 (a prodrug of BMS‐819881) (Washburn et al , ) (an overview of the observed findings is available at http://www.ncats.nih.gov/files/BMS-830216.pdf). No decrease in body wt or food intake could be observed in the study, but no data on the CNS behaviour of BMS‐830216/BMS‐819881 in man have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration at 30 mg/kg qd of 1b as the glycine pro-drug 40 for four days to young growing SD rats produced a statistically insignificant 1.8% reduction in weight gain whereas the structurally similar thienopyrimidinone standard 41 (rat K i = 7.2 nM) (compound 19 in Ref. 4) caused a significant 6.2% decrease when administered as the glycine pro-drug 42 at 10 mg/kg (Fig. 3).…”
Section: Mchr1 Receptor Antagonists Dihydropyrrolopyrazolonesmentioning
confidence: 97%
“…1). 4 A projected human efficacious dose of 400 mg qd and a long half-life led to a follow-up focus toward identifying more potent analogues that would lower the projected human dose and possess a shorter t 1/2 . In an effort to expand upon our discovery that nonbasic entities containing a thienopyrimidine core were potent MCHR1 antagonists, multiple non-basic counterparts containing bicyclo[3.3.0] cores were explored.…”
mentioning
confidence: 99%
“…1) had suggested a general need for free drug concentrations in the brain to be above the drug's K i value at trough. 2 In addition, factors such as receptor occupancy and slower off-rates play a role in determining efficacy in reducing weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolotriazinones (2) were prepared via amination of pyrazole ester 20 7 with chloramine in high yield followed by transformations analogous to the ones described in earlier schemes (see Scheme 4).…”
Section: Introductionmentioning
confidence: 99%